PEMEROLEHAN BAHASA KEDUA PADA ANAK USIA SD MELALUI KEGIATAN MENONTON SERIAL UPIN IPIN DI TELEVISI - MARWANI MARWANI (BASA Journal of Language & Literature, 2022)
Language Aquisition or commonly referred to as language acquisition is very important in human life. Language is a means of communication when interacting with others, which must be mastered by humans from an early age. Language acquisition and good language mastery mastered from an early age can support the quality of human life, especially in the aspect of social interaction with others. Therefore, given the importance of early language acquisition, language acquisition in children is important to learn. This article will present some brief reviews of language acquisition in terms of design and how language acquisition in children is obtained through electronic media, namely by watching the Upin Ipin animated series on television. The source of data in this study is the "Upin Ipin" series, chosen by the author because this animated series is much favored by children, especially elementary school age. The purpose of this research is to describe language acquisition in children and its influence on children's psychology through the animated series "Upin Ipin" in terms of linguistics, namely phonology, morphology, syntax. The method used in this research is qualitative method with case study approach. The results obtained in this study, among others, in terms of phonology, children can be said to be fluent in pronouncing vowels and consonants clearly. In terms of morphology, children have not used systematic sentences. From the syntactic level, they have produced adjective, noun and verb phrases. Through watching the Upin Ipin animated television series, eight-year-old children have the ability to use deixis in their speaking activities, both conversations with peers and with parents.